2009
DOI: 10.1016/j.tet.2008.10.113
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)-catalyzed hydration of allenes

Abstract: A gold(I) N-heterocyclic carbene complex catalyzes the intermolecular hydration of allenes to form allylic alcohols in modest yield with selective delivery of water to the terminal carbon atoms of the allenyl moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Saito et al. described the use of [Ru 3 (CO) 10 ] to promote the formation of methyl and γ,δ‐unsaturated ketones in the presence of trifluoroacetic acid, whereas Widenhoefer and co‐workers demonstrated the gold‐mediated generation of allylic alcohols …”
Section: Methodsmentioning
confidence: 99%
“…Saito et al. described the use of [Ru 3 (CO) 10 ] to promote the formation of methyl and γ,δ‐unsaturated ketones in the presence of trifluoroacetic acid, whereas Widenhoefer and co‐workers demonstrated the gold‐mediated generation of allylic alcohols …”
Section: Methodsmentioning
confidence: 99%
“…[93] When water was used as the nucleophile, the hydration of allenes in the presence of [AuCl(IPr)]/AgOTf afforded E-allylic alcohols efficiently. [94] The addition usually took place at the less sterically hindered C=C bond of allenes. However, DFT calculations have suggested that the tertiary allyl ether should be the kinetic product, and subsequent gold-catalyzed isomerization possibly occurs to produce the observed (and more stable) primary allylic ether.…”
Section: Transition-metal-catalyzed Additions Ofmentioning
confidence: 99%
“…Transition metal catalysed reaction of allenes [26][27][28][29][30][31][32][33][34] with nucleophiles is one of the most representative examples where the choice of metal has profound implications in the outcome and selectivity, including enantioselectivity, of the reaction [35][36][37][38][39][40][41][42]. For example, the intermolecular reaction of allenes with palladium or gold catalysts in the presence of oxygen nucleophiles gives allyl ethers with the regioselectivity of the addition controlled by the substitution on the allene and the reaction conditions (Scheme 1a and b) [43][44][45][46][47][48][49][50][51][52]. However, reported examples of the reaction in the presence of rhodium give preferentially vinyl ethers by attack of the nucleophile to the central carbon of the allene (Scheme 1c) [53].…”
Section: Introductionmentioning
confidence: 99%